Measure dynamic individual spatial-temporal accessibility by public transit: Integrating time-table and passenger departure time. (January 2018) - Cheng, Shaowu; Xie, Bing; Bie, Yiming; Zhang, Yaping; Zhang, Shen
Abstract: The spatial–temporal accessibility of a transport system assesses the spatial–temporal constraints faced by individuals based on their fixed activities and the ability of the transport system to facilitate trading time for space in movement. Previous studies either measured the individual spatial–temporal accessibility of a general transport network or measured the cumulative-opportunity accessibility by public transit through an exclusive computation of the bottom of the full network time prism. By contrast, the current study measures the individual spatial–temporal accessibility by public transit by integrating timetable and passenger departure time and computing the full network time prism. A public transit network is modelled as a time-dependent weighted directed graph, wherein every single directed arc is associated with a time-dependent travel time to represent the linkage between two adjacent stops on a transit route. The time-dependent travel time assigned to arcs is determined according to timetables, which is particularly assigned to infinity when transit service is unavailable between two stops. A modified network potential path area (N-PPA) algorithm based on the time-dependent weighted directed graph is employed to produce a potential path area for the activity participation of an individual by public transit. The proposed methodology is applied as a case study to measure individual spatial–temporal accessibility using the Salt Lake City TRAX system. Results indicate that the outcome of the proposed methodology is sensitive to departure time of passengers. The results of this study provide suggestions on potential improvement of bus/rail line layout and timetables and may aid in trip planning of passengers.